2013
DOI: 10.1590/s0103-90162013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Honey and propolis production, hygiene and defense behaviors of two generations of Africanized honey bees

Abstract: Phenotypic characters of honeybees, relevant to beekeepers, can be evaluated by studying correlations between them, and the correlated characteristics can be evaluated in the short term to assist in monitoring of annual genetic progress. This work therefore aims to evaluate the production of honey and propolis, the hygiene and defensive behaviours of two generations of Africanized Apis mellifera (Hymenoptera, Apidae), to estimate the correlations between them and their heritability. We used 30 Langstroth beehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
(37 reference statements)
3
18
1
Order By: Relevance
“…We noted that the colonies showed similar patterns; however, this differed from reports in the literature (Nascimento et al, 2008). These results could be ascribed to environmental factors (temperature, humidity, and atmospheric pressure) and/or genetic factors (Garcia et al, 2013). Therefore, it is arguable that the similarities in the defensive behaviors seen in the colonies used here allow this study to avoid possible genetic effects that could influence our results.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We noted that the colonies showed similar patterns; however, this differed from reports in the literature (Nascimento et al, 2008). These results could be ascribed to environmental factors (temperature, humidity, and atmospheric pressure) and/or genetic factors (Garcia et al, 2013). Therefore, it is arguable that the similarities in the defensive behaviors seen in the colonies used here allow this study to avoid possible genetic effects that could influence our results.…”
Section: Discussionmentioning
confidence: 86%
“…The hygienic behavior of all colonies (control and treatment) was analyzed by the method of drilling of capped brood, in accordance with the method described by Garcia et al (2013). In treatment colonies, after apitoxin harvest, a frame with capped brood areas of each colony was selected, and two different areas containing approximately 100 cells (area A and B) were marked.…”
Section: Methodsmentioning
confidence: 99%
“…This tendency was not found by Garcia et al (2013), who only tested colonies selected for high propolis production. In our study, we also included and compared colonies selected for low propolis production, which allowed us to differentiate the degree of hygienic behavior as a function of propolis production tendencies.…”
Section: Discussionmentioning
confidence: 86%
“…When we consider the advantages for the colony of propolis in the hive and the possibility of economic gain from selling this product, it is clear that selection for propolis production is desirable and viable, especially given the high degree of heritability (h 2 = 0.87) for this characteristic (Garcia et al, 2013). Hygienic behavior also has a high heritability rate, ranging from 0.52 to 0.65 (Rinderer, 1986;Harbo and Harris, 1999;Garcia et al, 2013). However, Garcia et al (2013) found no significant correlation between propolis production and hygienic behavior, which would make indirect selection for one of the characteristics by selecting for the other unviable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation